Glucose-6-phosphate dehydrogenase (G6PD). Response of the human erythrocyte and another cells to the decrease in their activity (2007)
Glucose-6-phosphate dehydrogenase is the first enzyme in the pentose phosphate pathway and the main intracellular source of reduced nicotidamineadenine nucleotidephosphate (NADPH), involved in diverse physiological processes such as antioxidant defense, (for instance in the erythrocyte) endothelial growth modulation, erithropoyesis, vascularization and phagocitosis, G6PDH deficiency is the most common X-chromosome-linked enzymopathy in human beings. Although it is present in any type cell, its absolute deficiency is incompatible with life. According to WHO, 400 million people are affected by G6PD deficiency in the world but in Colombia, the severe form prevalence is about 3% to 7%. There are no data related to slight and moderate alterations, that also have clinical effects. This paper reviews some G6PD biomolecular aspects, its classification according to activity and electrophoretic mobility, as well as some main clinical aspects related to its activity alteration. © 2007 Corporación Editora Médica del Valle.